The Effects of a Pilot Intervention for Community-Dwelling Adults with Rheumatoid Arthritis in Wuhan, China - Deng, Wenfang; Hu, Jie (Frontiers in Public Health, 2013)
This study examined the effects of a pilot educational intervention program on knowledge, perceived self-efficacy and health-related quality of life of community-dwelling adults with rheumatoid arthritis. A convenience sample of 16 participants with rheumatoid arthritis completed the program in Wuhan, China. Data were collected in face-to-face interviews using questionnaires at baseline, post-test and 1 month follow-up. Knowledge scores were significantly increased over time. Significant differences were found in pain self-efficacy, symptoms self-efficacy, bodily pain, social functioning and role emotional functions. Community health providers should provide educational programs to improve health-related quality of life for adults with rheumatoid arthritis.